2022
DOI: 10.1038/s41398-022-01810-7
|View full text |Cite
|
Sign up to set email alerts
|

Patient–clinician brain concordance underlies causal dynamics in nonverbal communication and negative affective expressivity

Abstract: Patient–clinician concordance in behavior and brain activity has been proposed as a potential key mediator of mutual empathy and clinical rapport in the therapeutic encounter. However, the specific elements of patient–clinician communication that may support brain-to-brain concordance and therapeutic alliance are unknown. Here, we investigated how pain-related, directional facial communication between patients and clinicians is associated with brain-to-brain concordance. Patient–clinician dyads interacted in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…Psychologists have found that various positive factors (somatosensory stimulation, enhanced doctor–patient relationships, and treatment context) in the healing ritual can contribute to a significant placebo effect [ 8 ]. Recent studies have suggested that this placebo effect for patient analgesia might be associated with dynamic patient-brain to clinician-brain concordance during patient–clinician interaction [ 86 , 87 ]. Furthermore, SA can also induce a physiological response that is similar to, but weaker than, that produced by RA, probably leading to a specific effect [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Psychologists have found that various positive factors (somatosensory stimulation, enhanced doctor–patient relationships, and treatment context) in the healing ritual can contribute to a significant placebo effect [ 8 ]. Recent studies have suggested that this placebo effect for patient analgesia might be associated with dynamic patient-brain to clinician-brain concordance during patient–clinician interaction [ 86 , 87 ]. Furthermore, SA can also induce a physiological response that is similar to, but weaker than, that produced by RA, probably leading to a specific effect [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a new paradigm, hyperscanning realizes the conversion of traditional “one‐person” approach to “two or more person” approach and the transformation from brain–computer interaction to brain–brain coupling, which greatly enhanced the research on inter‐personal brain mechanism (Gvirts & Perlmutter, 2020 ; Schilbach et al, 2013 ). Recently, using hyperscanning techniques to reveal the influence of patient–doctor interaction on clinical outcomes attracts growing attention (Anzolin et al, 2020 ; Crum et al, 2022 ; Ellingsen et al, 2020 ; Ellingsen et al, 2022 ). For example, an fNIRS hyperscanning study reported that INS in the PFC of patient–doctor pair was significantly greater during clinical interactions compared to everyday‐life communication (Crum et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The blue and red curves represent the HbO time series from the ROI_1 of "patient" and acupuncturist, respectively. HbO, oxyhemoglobin; ROI, region of interest the influence of patient-doctor interaction on clinical outcomes attracts growing attention (Anzolin et al, 2020;Crum et al, 2022;Ellingsen et al, 2020;Ellingsen et al, 2022). For example, an fNIRS hyperscanning study reported that INS in the PFC of patientdoctor pair was significantly greater during clinical interactions compared to everyday-life communication (Crum et al, 2022).…”
Section: Hyperscanning Studies Reveal the Inter-brain Neural Synchron...mentioning
confidence: 99%
See 1 more Smart Citation
“…In a therapeutic setting involving hyperscanning, there are potential opportunities for both the patient and therapist to detect dyadic influences on neural activation (Figure 2). One study found that brain-to-brain concordance between the mid/posterior insular cortex of the patient and the anterior insular cortex of the therapist were positively associated with subjective assessments of therapeutic alliance [Ellingsen et al 2022]. Another study showed that among therapist and chronic pain patient dyads, brain-to-brain concordance in networks involved in mentalizing and social mirroring resulted in increased patient analgesia [Ellingsen et al 2020].…”
Section: Incorporating Neurofeedback Into Therapist-patient Communica...mentioning
confidence: 99%